Digital Skills Assessments in Occupational Therapy: A Scoping Review. - Segal, Addie; Doyle, Nancy W.; Yaffe, Yuval (American Journal of Occupational Therapy)
Importance: Digital skills are increasingly essential in performing daily activities. Occupational therapy practitioners require valid and accessible assessments to evaluate and address these competencies. However, the availability and quality of these assessments have not been established. Objective: To identify and map existing, accessible, low-cost measures to assess digital skills in adult populations, supporting occupational therapy practitioners. Data Sources: Literature searches were conducted using the CINAHL, PsycINFO, and PubMed/MEDLINE databases and the American Journal of Occupational Therapy archives, supplemented with Google Scholar and online resources covering 2000 to May 2024. Study Selection and Data Collection: This review followed the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) checklist. It included tools for adults ages 18 yr and older that were published in English, available online or through author contact, and free or low cost. Tools requiring substantial training or high cost were excluded. Two reviewers independently screened records for inclusion; a third reviewer verified final selections against the criteria. Findings: Twenty-seven assessments were included, covering the Computer Skills, Mobile and Tablet Skills, Technology and Internet Skills, Technology Proficiency for Students, and IADLs domains. Most demonstrated high reliability (Cronbach's α >.80) and validity; however, normative data and test–retest reliability were limited. Notably missing were assessments of touchscreen skills, online safety, and artificial intelligence competency. Conclusions and Relevance: This review identified multiple validated and accessible assessments for clinical practice; however, significant gaps remain. Future studies should address these gaps to enable comprehensive evaluation of and intervention for emerging digital competencies in occupational therapy. Plain-Language Summary: This review examined assessments that can be used by occupational therapy practitioners to measure the digital skills adults need for various daily tasks. Twenty-seven practical tools were identified, with most being reliable and easy to use. However, there is a lack of tools addressing touchscreen skills, internet safety, and artificial intelligence use. Filling these gaps will help occupational therapy practitioners better support clients in their daily digital activities. This review examined assessments that can be used by occupational therapy practitioners to measure the digital skills adults need for various daily tasks.